A Citrullus colocynthis fruit extract acutely enhances insulin-induced GLUT4 translocation and glucose uptake in adipocytes by increasing PKB phosphorylation. (24th April 2021) - Drissi, Farah; Lahfa, Farid; Gonzalez, Teresa; Peiretti, Franck; Tanti, Jean-François; Haddad, Mohamed; Fabre, Nicolas; Govers, Roland
Abstract: Ethnopharmacological relevance: Citrullus colocynthis (L.) Schrad is a common fruit in traditional medicine and used as remedy against various diseases, especially diabetes. Up to now, its anti-diabetic effects have been fully attributed to its enhancement of pancreatic insulin secretion. Whether C. colocynthis also ameliorates insulin action in peripheral tissues has not been investigated. Aim of the study: In the present study, using 3T3-L1 adipocytes as cell model, we have investigated whether colocynth fruit extracts affect insulin action. Materials and methods: Various extracts were prepared from the C. colocynthis fruit and screened using a cell-based 96 well plate GLUT4 translocation assay. Promising extracts were further studied for their effects on glucose uptake and cell viability. The effect on insulin signal transduction was determined by Western blot and the molecular composition was established by LC-MS. Results: The ethyl acetate fractions of aqueous non-defatted extracts of seed and pulp, designated Sna1 and Pna1, acutely enhanced insulin-induced GLUT4 translocation. In accordance, both extracts increased insulin-stimulated cellular glucose uptake. Pna1, which displayed greater effects on GLUT4 and glucose uptake than Sna1, was further investigated and was demonstrated to increase GLUT4 translocation without changing the half-maximum dose (ED50) of insulin, nor changing GLUT4 translocation kinetics. At the molecular level, Pna1 was found to enhance insulin-induced PKB phosphorylation without changing phosphorylation of the insulin receptor. Pna1 appeared not to be toxic to cells and, like insulin, restored cell viability during serum starvation. By investigating the molecular composition of Pna1, nine compounds were identified that made up 87% of the mass of the extract, one of which is likely to be responsible for the insulin-enhancing effects of Pna1. Conclusions: The C. colocynthis fruit possesses insulin-enhancing activity. This activity may explain in part its anti-diabetic effects in traditional medicine. It also identifies the C. colocynthis as a source of a potential novel insulin enhancer that may prove to be useful to reduce hyperglycemia in type 2 diabetes. Graphical abstract: Image 1 Highlights: In traditional medicine, the colocynth is known for its anti-diabetic properties. Colocynth fruit extract Pna1 acutely enhances insulin-induced GLUT4 translocation. Pna1 acutely increases cellular glucose uptake in insulin-stimulated cells. Pna1 enhances insulin action by increasing protein kinase B (PKB) phosphorylation. Our study may explain the anti-diabetic properties of the colocynth.